Echinococcus granulosus: The establishment of the metacestode in the liver is associated with control of the CD4+ T-cell-mediated immune response in patients with cystic echinococcosis and a mouse model - Hou, Xinling; Shi, Yang; Kang, Xuejiao; Rousu, Zibigu·; Li, Dewei; Wang, Maolin; Ainiwaer, Abidan·; Zheng, Xuran; Wang, MingKun; Jiensihan, Bahejiang·; Li, Liang; Li, Jing; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The larval stage of the tapeworm Echinococcus granulosus sensu lato (E. granulosus s.l.) caused a chronic infection, known as cystic echinococcosis (CE), which is a worldwide public health problem. The human secondary CE is caused by the dissemination of protoscoleces (PSCs) when fertile cysts are accidentally ruptured, followed by development of PSCs into new metacestodes. The local immune mechanisms responsible for the establishment and established phases after infection with E. granulosus s.l. are not clear. Here, we showed that T cells were involved in the formation of the immune environment in the liver in CE patients and Echinococcus granulosus sensu strict (E. granulosus s.s.)-infected mice, with CD4+ T cells being the dominant immune cells; this process was closely associated with cyst viability and establishment. Local T2-type responses in the liver were permissive for early infection establishment by E. granulosus s.s. between 4 and 6 weeks in the experimental model. CD4+ T-cell deficiency promoted PSC development into cysts in the liver in E. granulosus s.s.-infected mice. In addition, CD4+ T-cell-mediated cellular immune responses and IL-10-producing CD8+ T cells play a critical role in the establishment phase of secondary E. granulosus s.s. PSC infection. These data contribute to the understanding of local immune responses to CE and the design of new therapies by restoring effective immune responses and blocking evasion mechanisms during the establishment phase of infection.